Age classes of developing Red-necked Spurfowl Pternistis afer based on plumage, morphology and behaviour. (4th May 2019) - van Niekerk, Johann H
Abstract : This paper describes the plumage and morphology development of 11 age classes of Red-necked Spurfowl Pternistis afer to assist with field observations. Sixteen spurfowl were marked with coloured leg rings in the Cannon Rocks Holiday Resort, Eastern Cape, South Africa during March 2006 and observed daily until June 2008 to describe plumage and non-plumage morphological changes. The age classes include natal chicks, six discernible juvenile phases, post-juvenile phase, near-adult phase, non-territorial and territorial males. Red-necked Spurfowl only attain the adult plumage phase at about 240 d. However, if the development of the bare red throat and spurs are excluded, this near-adult plumage stage is attained at about 180 d. Territorial male Red-necked Spurfowl have long spurs similar to other Pternistis spp. The cryptic downy pattern of chicks assist the birds to blend in with their habitat. However, the plumage of juveniles is simply a transitional phase between the cryptic plumage of downy chicks and the less cryptic plumage of adult spurfowls.